High temperature dynamic response of SPS-processed Ni3Al. (November 2018) - Frage, N.; Kalabukhov, S.; Wagner, A.; Zaretsky, E.B.
Abstract: To clarify mechanisms governing plastic deformation in SPS-processed Ni3 Al, the temperature-dependence of its yield strength was determined at temperatures up to 1200 K. Based on these measurements, the evolution of elastic-plastic waves with propagation distance in samples of Ni3 Al was studied at room temperature and at 923 K, the temperature at which maximum yield strength is seen. The differences between temperature dependencies of yield strength measured under dynamic and static conditions can be explained as being the result of competition between primary (octahedral planes) and secondary (cubic planes) dislocation glide systems. It can be argued that the former thermally hardens the intermetallic, whereas the latter is responsible for its thermal softening. Since the secondary glide system prevails at high temperature, the stress τ ∗ ≅ 0.55 GPa, corresponding to the change in regime of decay of the elastic wave at 923 K, seems to be equal the Peierls stress of dislocation of 〈 110 〉 { 100 } glide systems at this temperature. Highlights: Impact response of Ni3Al over 300–1200 K temperature interval. Difference between static and dynamic yield strengths and its explanation. Determination of the Peierls stress of 〈110〉{100} glide system at 900 K.